2020
DOI: 10.3389/fmicb.2020.01634
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of the Class IIa Bacteriocins, Plantaricin 423 and Mundticin ST4SA, in Escherichia coli Using Green Fluorescent Protein as a Fusion Partner

Abstract: The antilisterial class IIa bacteriocins, plantaricin 423 and mundticin ST4SA, have previously been purified from the cell-free supernatants of Lactobacillus plantarum 423 and Enterococcus mundtii ST4SA, respectively. Here, we present the fusions of mature plantaricin 423 and mundticin ST4SA to His-tagged green fluorescent protein (GFP) for respective heterologous expression in Escherichia coli. Fusion of plantaricin 423 and mundticin ST4SA to His-tagged GFP produced the fusion proteins GFP-PlaX and GFP-MunX, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Bacteriocin screening via BAGEL4 revealed that AGA58 predicted to carry 3 core bacteriocin biosynthesis genes in the same operon (Fig 4). The protein sequence encoding A2 lantipeptide did also show around 80% similarity with Plantaricin_423 peptide which is known to harbor anti-listerial activity [35]. However, performing a protein blast of the sequence [ MKKEIELSEKELVRII GG KYYGNGVSCTKKHGCKVNWGQAFTCSVNRFANFGHGNC] in NCBI showed that it has the highest sequence homology with A2 lantipeptide (Table S2, supplemental).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteriocin screening via BAGEL4 revealed that AGA58 predicted to carry 3 core bacteriocin biosynthesis genes in the same operon (Fig 4). The protein sequence encoding A2 lantipeptide did also show around 80% similarity with Plantaricin_423 peptide which is known to harbor anti-listerial activity [35]. However, performing a protein blast of the sequence [ MKKEIELSEKELVRII GG KYYGNGVSCTKKHGCKVNWGQAFTCSVNRFANFGHGNC] in NCBI showed that it has the highest sequence homology with A2 lantipeptide (Table S2, supplemental).…”
Section: Resultsmentioning
confidence: 99%
“…The fused proteins were inactive, and it was necessary to purify and cleave the fused proteins to obtain pure PapA mature peptide. Then, the pure PapA peptide can inhibit L. monocytogenes [ 25 , 27 , 28 ]. The class IIα bacteriocins are produced as prebacteriocin with an N-terminal extension, which is removed by site-specific proteolytic cleavage during export.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli , a periplasmic leaky E. coli strain had to be used to express and secrete the chimeric protein into the medium, which displayed listericidal activity. The pedA gene was also fused with the dihydrogolate reductase ( DHFR ) gene [ 25 ], the thioredoxin ( Trx ) gene [ 26 , 27 ], and the green fluorescent protein ( GFP ) gene [ 28 ] on the 5´ side. The fused protein had no biological activity after IPTG induction.…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, papA in fused protein was inactive, which had to be cut from the fused protein to get pure papA mature peptide [9,11,17]. The pure papA peptide possessed anti-listeria active.…”
Section: Discussionmentioning
confidence: 99%
“…Pediocin gene has been introduced to lactococcus lactis [6], and E. coli [7,8], where the ABC transporter protein and secretion apparatus-genes or other secretion apparatus were necessary for active peptide. To overcome this shortage, pedA gene was fused with dihydrogolate reductase (DHFR) gene [9], thioredoxin (Trx) gene [10], green uorescent protein (GFP) gene [11] on the 5´ side. The fused protein had no biological activity after IPTG induction.…”
Section: Introductionmentioning
confidence: 99%